2014
DOI: 10.1105/tpc.114.123737
|View full text |Cite
|
Sign up to set email alerts
|

OPT3 Is a Phloem-Specific Iron Transporter That Is Essential for Systemic Iron Signaling and Redistribution of Iron and Cadmium inArabidopsis   

Abstract: Iron is essential for both plant growth and human health and nutrition. Knowledge of the signaling mechanisms that communicate iron demand from shoots to roots to regulate iron uptake as well as the transport systems mediating iron partitioning into edible plant tissues is critical for the development of crop biofortification strategies. Here, we report that OPT3, previously classified as an oligopeptide transporter, is a plasma membrane transporter capable of transporting transition ions in vitro. Studies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
252
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(266 citation statements)
references
References 73 publications
(111 reference statements)
12
252
2
Order By: Relevance
“…This suggests that the phloem Fe compound acting as a repressive signal could be a peptide (probably a Fe-peptide) transported by OPT3 [82,87]. However, recently it has been published that OPT3 could transport Fe ions into the phloem [89]. Even if these results are confirmed, it would not be ruled out that the Fe ions, once inside the phloem, could be bound to organic compounds to be transported.…”
Section: Hormones and Signaling Substances In The Regulation Of Fe Ancontrasting
confidence: 39%
See 1 more Smart Citation
“…This suggests that the phloem Fe compound acting as a repressive signal could be a peptide (probably a Fe-peptide) transported by OPT3 [82,87]. However, recently it has been published that OPT3 could transport Fe ions into the phloem [89]. Even if these results are confirmed, it would not be ruled out that the Fe ions, once inside the phloem, could be bound to organic compounds to be transported.…”
Section: Hormones and Signaling Substances In The Regulation Of Fe Ancontrasting
confidence: 39%
“…Even if these results are confirmed, it would not be ruled out that the Fe ions, once inside the phloem, could be bound to organic compounds to be transported. Taken together, the results obtained with the frd3 and opt3-2 mutants suggest that Fe availability, represented by a phloem Fe-related signal, could participate in the regulation of Fe acquisition genes in roots along with ethylene and other hormones [82,89,90].…”
Section: Hormones and Signaling Substances In The Regulation Of Fe Anmentioning
confidence: 62%
“…Several reports have indicated the importance of proper loading of metal ions into seeds for successful plant reproduction. The role of YSL (AtYSL1 and AtYSL3) and the oligopeptide transporter (AtOPT3) protein family in iron translocation to developing embryo and into the seed coat is critical for reproductive growth (Le Jean et al, 2005;Stacey et al, 2008;Chu et al, 2010;Mendoza-Cózatl et al, 2014;Zhai et al, 2014). Additionally, the role of Arabidopsis thaliana FERRIC REDICTASE DEFECTIVE3 (AtFRD3) in iron acquisition in reproductive tissues such as pollen grain and embryos suggests a complex mechanism of iron nutrition during embryogenesis (Roschzttardtz et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of our RNA-seq data revealed that the expression of several genes from (A) Seeds of the indicated plant lines were germinated and grown in soil, and fertilized with the N-P-K fertilizer and a standard nutrient solution (Zhai et al, 2014). Note the retarded growth of the citf1 spl7 double mutant seedling (inside a white square) that eventually died.…”
Section: Citf1 and Spl7 Are Required For Cu Delivery To Flowersmentioning
confidence: 99%
“…Different Arabidopsis plant lines were grown either on solid 0.53 Murashige and Skoog (MS) medium (pH 5.7) (Murashige and Skoog, 1962) or hydroponically (Zhai et al, 2014). For growing plants on solid medium, seeds were surface-sterilized as described (Zhai et al, 2014).…”
Section: Growth Conditions and Experimental Treatmentsmentioning
confidence: 99%